SISTEM ANTI VIRUS MENGGUNAKAN METODE CYCLIC REDUNDANCY CHECKSUM-32 “GnR-AV” - GHONIY ROSYIDDIN; KIKIM MUKIMAN (KILAT, 2015)
Computer viruses can damage the nature example by destroying the data on the document, make computer users feel disturbed by its presence in a computer system, and does not cause deleterious effects at all. Antivirus or Virus Protection Software is a type of software that is used to detect and remove computer viruses from the computer system. Software process models used are linear or sequential process model Waterfall. Linear sequential model proposes an approach to software development that is systematic and sequential starting at the level and progress of the whole system analysis, design, code, test, and maintenance. The resulting software is virus and antivirus applications. Virus application can be called with Qvir, while for the antivirus can be called with antq. Qvir built with Delphi 7, while antq built with Visual Basic 6. Testing of the software is done by the method of blackbox. The objective of this antiviral is to determine the gaps that have the potential to be used viruses that could undermine the security of computer systems that are used, while the purpose of the antivirus that is to cover the gap from the computer system and the gaps not addressed by other antivirus, so that the virus can not be entry and damage to the computer system